Design of risk management matrices to validate the aseptic process of injectable solutions - Bravo, Gustavo V. (2019)
Quality Risk Management (QRM) in the pharmaceutical industry and especially in the manufacture of sterile products is of vital importance for its impact on health. The objective of this work is, to design and jointly apply risk management matrices to validate the aseptic process of injectable solutions. For the design of the Simulated Aseptic Process (APS) the following risk matrices were developed: Risk matrix for the determination of the worst case; Time matrix of the simulated aseptic process; Risk Matrix of Failure Mode and Effect Analysis (FMEA); Risk matrix routine and non-routine interventions. It is concluded that the joint and complementary use (not exclusive) of the risk analysis tools of this work and their respective matrices is a guide that helps methodologically to discern the risk and contribute to properly manage the APS. Likewise, the incorporation of the matrices of systematic follow-up of the interventions during the APS is key, since the human factor is the main vector of contamination. The results of the application of the risk matrices of the present work in the continuous APS carried out, in the three runs, were in accordance with the specifications.